2021
DOI: 10.1097/cce.0000000000000582
|View full text |Cite
|
Sign up to set email alerts
|

Teleguidance Technology for Endotracheal Intubation: A Scoping Review

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Adult studies demonstrate that technology is available to provide a remote clinician with a view of a videolaryngoscope screen during a two-way communication. Review of 12 simulation studies and five clinical studies on teleguidance-facilitated intubation found the practice feasible, safe and efficacious in adult practice 30. Two studies showed higher first attempt success rates and a faster time to intubation with telemedicine-supported intubation, compared with standard care.…”
Section: Methodsmentioning
confidence: 98%
“…Adult studies demonstrate that technology is available to provide a remote clinician with a view of a videolaryngoscope screen during a two-way communication. Review of 12 simulation studies and five clinical studies on teleguidance-facilitated intubation found the practice feasible, safe and efficacious in adult practice 30. Two studies showed higher first attempt success rates and a faster time to intubation with telemedicine-supported intubation, compared with standard care.…”
Section: Methodsmentioning
confidence: 98%
“…It also facilitates progressive autonomy for airway trainees. [ 35 ] However, clinical studies are necessary to fully understand the benefits and limitations of this technology.…”
Section: Newer Tools and Techniques For Airway Managementmentioning
confidence: 99%
“…Lastly, hospital administrators are also considered part of the ART, and their role is to invest in resource allocation, training programs, and education of ART staff. Telemedicine may play an emerging role in managing ARTs in settings where expertise is not readily available [ 31 , 32 ].…”
Section: The Team Modelmentioning
confidence: 99%